The impact of Internet use on labor wage distortions: Empirical Evidence From China. (May 2022) - Zhao, Xin; Jiao, Yishuo; Wu, Dan
With the general growth of human capital, it is urgent to reduce and eliminate the distortion of labor factor allocation, which may cause the loss of productivity. This study focuses on whether internet use has a moderating effect on labor wage distortion and its mechanism. Based on the national China Family Panel Studies survey in 2016, the study uses a stochastic frontier approach. The results show that the degree of average wage distortion in the labor market ranged from 45.02% to 55.24%, while internet use alleviated wage distortion by 3.76% on the whole. This reduction was maintained after treatments for endogeneity and tests for robustness. Internet use effectively reduced wage distortion through educational matching, employment security, and job expectation.